Way Leman River Flood Control in Buru Regency - Nara, Obednego D; Hutubessy, Vector R.R; Soumokil, Musper D (International Journal of Advanced Engineering Research and Science, 2022)
Way Leman River is located at the watershed of Way Leman covering with an area of 167.24 Km2. During the rainy season the Way Leman river flow has the potential to disrupt community activities. Material losses and crop failure are inevitable in the event of a flood. Therefore, it is necessary to identify the cause of the disaster. From the rainfall data usedat the climatology (BMKG) Namlea station for 20 years, namely in 2000 - 2019, statistically with the Gumbel distribution for the 25yearsreturn period, the planned rainfall250.31 mm /year and the Melchior method found a planned flood discharge of 290.85 m3/sec. From the simulation results of the Way Leman river cross section using the 25-Year Planned Debit with the Melchior Method, it cannot accommodate the flood discharge that occurs because the elevation of the flood water level exceeds the elevation of the river bank. In order to control the flood, the Way Leman river was normalized and made a river reinforcement building with gravity wall type. The results of analysis showed that the selection of the type of structure was permitted.